No Need to Worry? Anxiety and Coping in the Entrepreneurship Process - Thompson, Neil A.; van Gelderen, Marco; Keppler, Laura (Frontiers in Psychology, 2020)
Understanding experiences of and responses to anxiety is foundational to developing robust theories of entrepreneurial behavior. Using open-ended, vignette and graphical elicitation interviews with 77 entrepreneurs, we inductively investigate the experience of and coping responses to anxiety during the entrepreneurship process. We develop a comprehensive and dynamic goal-striving model to explain experiencing and coping with entrepreneurial anxiety by integrating empirical findings with appraisal and control theories. In doing so, we theorize that entrepreneurial anxiety is endogenous to a cyclical conception of goal-striving, such that various sources of anxiety make sense only in consideration of the goals, standards or values to which they pertain. In this regard, entrepreneurs’ coping responses influence four different points of an iterative goal-striving cycle—an insight that moves beyond problematic static and binary coping classifications.